Environmental conditions of the landscape functioning in the Pribaikalskii National Park: historical perspective. Issue 1 (November 2021) - Atutova, Zh V; Li, Zehong
Abstract: The history of the economic development of the valley complexes of the Goloustnaya River basin is considered. Forestry and agricultural activities are designated as the main activities developed by the local population. Fluctuation changes in the intensity of their implementation are highlighted, specifically. the slowly developing process of economic development of valley landscapes due to low population in the second half o f the 17 th century and until the first half of the 20 th century; expansion of agricultural land and growth of industrial development of forest resources, starting from the middle of the 20 th century until the end of the 1980s; and a decrease in economic activities since the end of the last century, which is connected both with the state reorganization of the country's economy and with creation of specially protected natural territories within the studied area. The valley complexes of the Goloustnaya River are at risk from the recreational development of coastal areas of Lake Baikal that have been actively developing in recent years. Taiga landscapes of the upper and middle reaches of the river are at risk of spreading forest fires. Negative consequences from economic activities have been contributing to a significant anthropogenic transformation of landscapes of the Pribaikalskii National Park for a long period.